2009
DOI: 10.1007/s11099-009-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dynamics of stomatal response to sudden increase in CO<sub>2</sub> concentration in maize supplied with different amounts of water

Abstract: Environmental factors that influence stomatal conductance (g s ) interact through a complex network of signal transduction and have therefore highly interdependent effect.In the present study we examined how plant water status affects stomatal sensitivity to the change of CO 2 concentration ([CO 2 ]). We investigated the short-term dynamic of stomatal response to a sudden [CO 2 ] increase (from 400 to 700 µmol(CO 2 ) mol -1 ) in maize supplied with different amounts of water (resulting ψ w = -0.35, -0.52 and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In addition, salinity resulted in dehydration at the cellular level, and thus significantly reduced the RWC in the leaves of S. argentea (Table 2). Hladnik et al (2009) reported that a fast stomatal reaction of water-deprived plants is predetermined by a low xylem water potential of the leaf. According to our results, the salinity-level increase progressively decreased g s in the leaves of S. argentea seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, salinity resulted in dehydration at the cellular level, and thus significantly reduced the RWC in the leaves of S. argentea (Table 2). Hladnik et al (2009) reported that a fast stomatal reaction of water-deprived plants is predetermined by a low xylem water potential of the leaf. According to our results, the salinity-level increase progressively decreased g s in the leaves of S. argentea seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf stomata control the exchange of water vapour and environmental CO 2 . Stomatal conductance (g s ) is an important parameter to describe the flux exchange between vegetation and atmosphere (Nicolás and Philippe 2009, Hladnik et al 2009, James 2004. The level of plant transpiration rate (E) can reflect plants' adaptive ability to the environment (Fung et al 1998).…”
Section: Introductionmentioning
confidence: 99%